Mechanisms for Modulating Anoikis Resistance in Cancer and the Relevance of Metabolic Reprogramming - Adeshakin, Funmilayo O.; Adeshakin, Adeleye O.; Afolabi, Lukman O.; Yan, Dehong; Zhang, Guizhong; Wan, Xiaochun (Frontiers in Oncology, 2021)
Cell attachment to the extracellular matrix (ECM) is the hallmark of structure-function stability and wellbeing. ECM detachment in localized tumors precedes abnormal dissemination of tumor cells culminating in metastasis. Programmed cell death is activated during tumorigenesis to clear off ECM detached cells via “anoikis”. However, cancer cells develop several mechanisms in abrogating anoikis, thus promoting their invasiveness and metastasis. Certain factors such as growth proteins, pH, transcriptional signaling pathways, and oxidative stress have been reported as drivers of anoikis resistance, hence enhancing cancer proliferation and metastasis. Recent studies also highlighted the key contributions of metabolic pathways enabling the cells to bypass anoikis. Hence, understanding the mechanisms driving anoikis resistance could help to counteract tumor progression and prevent metastasis. This review elucidates the dynamics which cancer cells employ to impede anoikis thus promoting proliferation, invasion, and metastasis. In addition, the authors have discussed other metabolic intermediates (especially amino acids and nucleotides) less explored, which could be crucial for anoikis resistance and metastasis.